A ordem política e a reforma universitária : o processo de federalização da Faculdade de Odontologia de Uberlândia (1968-1978) - Pereira, Wander (2012)
The present thesis is integrated with the activities of the research History and Historiography of Education Graduate Program Doctorate in Education at the Federal University of Uberlândia and tied to Concentration Area: School Education. The research that gives rise to the work under discussion has focused on the historical process of the genesis, development and consolidation of the School of Dentistry, Uberlândia. Our work is inscribed in the story mode of. The purpose of conducting the research work resulted in the seizure of social representations focused on the process that gave rise to higher education in Uberlândia. The time frame of this study delineated between 1968 - the year that the university reform Law 5540/68 - and extends until 1978, when it occurs the federalization of the University of Uberlândia. With regard to the sources, there are the specific documents at the School of Dentistry such as books, records, correspondence with the Ministry of Education, the period studied law and political representatives and the region's education, facts of the time, who they portray the first classes in physical structure and initial architecture which marked the opening of the School of Dentistry. Another valuable source for the execution of the research was the press represented here by the newspapers of the time, namely: The Courier of Uberlândia, The Triangle and The Reporter. Deserves mention other official documents from the government constituted, as the minutes from the town hall of Uberlândia. The desk research and the taking of testimony was accompanied by the theoretical work of the research foundation, we serve both for us and also specializes vast bibliography of scholarly works that deal with the city of Uberlândia with emphasis on the social, economic, political and cultural. The methodology used is one which conforms to the peculiarities of the object of research, therefore, we approach the study as part of Cultural History and History Roger Chartier educational institutions grounded in Justin Magellan. A proper understanding of the history of Brazilian education has in the history of educational institutions a fruitful field for the Brazilian university, compared to European universities, is quite recent, and this sort, there is much to be done in this field of historiography. Thus, it creates an epistemic openness that justifies the study of the Faculty of Dentistry, as if it were not said the last words on the major institutions in Brazil, one can say that little has been written about the colleges that are in the country. The research results show that the genesis / development and consolidation of the School of Dentistry belongs to a good time in Brazil's history - the military regime and its interference in society, politics and education. The thesis emphasizes the subordination of academic practice to politics, which at that time was run by the expansion and development policy and internalization of higher education in Brazil. Therefore, sources indicate that the School of Dentistry installed in Uberlândia, Minas Gerais, fits in the context of training of technical personnel / graduate to work, if not immediately, at least in the short-term projects in the composition of the required professional for the development of the city. Thus, whether the individual colleges, is the Faculty of Dentistry, which occurred in Uberlândia was the realization of the intent of the civil society represented by its political class and the local groups, and shall have the membership of the youth who longed for university education.